2020
DOI: 10.1136/bmjopen-2019-035283
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for funders in monitoring compliance with policies on clinical trials registration and reporting: analysis of funding and registry data in the UK

Abstract: ObjectivesTo evaluate compliance by researchers with funder requirements on clinical trial transparency, including identifying key areas for improvement; to assess the completeness, accuracy and suitability for annual compliance monitoring of the data routinely collected by a research funding body.DesignDescriptive analysis of clinical trials funded between February 2011 and January 2017 against funder policy requirements.SettingPublic medical research funding body in the UK.Data sourcesRelevant clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Furthermore, public funders and institutional publication funds could demand that trial sponsors post their results before allocating funding for academic (open-access) publication. These funding bodies could also deny individual sponsors funding if they have violated clinical trial reporting rules in the past [37], an option currently being considered by some UK funding bodies. At the very least, journals should conform to the CONSORT statement in ensuring that registry identification numbers are clearly indicated in the abstract, full-text and meta-data of published clinical trials in order promote discoverability and record linkage between registries and publications [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, public funders and institutional publication funds could demand that trial sponsors post their results before allocating funding for academic (open-access) publication. These funding bodies could also deny individual sponsors funding if they have violated clinical trial reporting rules in the past [37], an option currently being considered by some UK funding bodies. At the very least, journals should conform to the CONSORT statement in ensuring that registry identification numbers are clearly indicated in the abstract, full-text and meta-data of published clinical trials in order promote discoverability and record linkage between registries and publications [35].…”
Section: Discussionmentioning
confidence: 99%
“…Such trials greatly outnumber trials of investigative medical products, and can be of equal or greater scientific and clinical importance; across Europe, they are most commonly registered on ClinicalTrials.gov , but also on other WHO primary registries such as ISRCTN and DRKS. Governments, regulatory agencies and research funders worldwide should extend registry reporting requirements to all interventional clinical trials as per WHO best practices [ 18 ]. We hope that our novel US clinical trials tracking tool ( clinical-trials-tracker.com ) will drive trial sponsors worldwide to exceed narrow regulatory compliance and fully implement WHO best practices to improve the completeness and accuracy of the medical evidence base and accelerate medical progress.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 39 ] clarified that CTs published in ICMJE member journals were highly compliant, but prospective trial registrations were still low. Furthermore, with regard to CTR after completion of a study, recent studies found that faster registration has become widespread [ 40 , 41 ]. These two factors are important for showing transparency in registration requirements.…”
Section: Discussionmentioning
confidence: 99%